1987
DOI: 10.1139/e87-209
|View full text |Cite
|
Sign up to set email alerts
|

The Holocene evolution of permafrost near the tree line, on the eastern coast of Hudson Bay (northern Quebec)

Abstract: Permafrost evolution in postglacial marine silts near the tree line was reconstructed using landform analysis, 14C dating, and palynostratigraphic analysis of peat sections. In the forest–tundra, below the tree line, four sites in peat plateaus have a stratigraphic sequence indicating an alluvial plain environment from 6000 to 4800 BP followed by a wetland supporting trees and shrubs with deep snow accumulation and without permafrost. Ground heave occurred between 1900 and 1200 BP as peat plateaus and palsas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 15 publications
2
46
0
Order By: Relevance
“…1), recorded a low lake level between 5300 and 4600 cal yr BP (Payette and Filion, 1993). Allard and Séguin (1987a) also documented this warm period in relation to the permafrost degradation near the tree line on the eastern coast of Hudson Bay between 4000 and 2500 cal yr BP. Synchronous warming was also recorded in lake sediment elsewhere in the northern hemisphere, e.g.…”
Section: Lacustrine Phasementioning
confidence: 81%
See 1 more Smart Citation
“…1), recorded a low lake level between 5300 and 4600 cal yr BP (Payette and Filion, 1993). Allard and Séguin (1987a) also documented this warm period in relation to the permafrost degradation near the tree line on the eastern coast of Hudson Bay between 4000 and 2500 cal yr BP. Synchronous warming was also recorded in lake sediment elsewhere in the northern hemisphere, e.g.…”
Section: Lacustrine Phasementioning
confidence: 81%
“…Ombrotrophication of peatland 6 km south of Lake Kaapumticumac was also linked to these cold conditions (Bhiry and Robert, 2006). Such conditions favored permafrost aggradation in subarctic Québec between 2500 and 2000 cal yr BP (Allard and Séguin, 1987a) in addition to alluvial fan activities in the Guillaume-Delisle area (200 km north of this site) (Lafortune et al, 2006). Despite the fact that it was difficult to pinpoint this event by examining lake sediments at the study site, natural lacustrine banks were observed in some areas around the lake.…”
Section: Lacustrine Phasementioning
confidence: 92%
“…The same studies concluded, through dating of the peat/lichen (water logged/dry) transition on top of many palsas that the permafrost started to form after 3200 BP and that particular periods (e.g. 1550-1000 BP and 500-100 BP or roughly the Little Ice Age) had a colder climate conducive to palsa formation (Heim, 1976;Allard et al, 1987a;Lavoie and Payette, 1995;Allard and Rousseau, 1999). Thermokarst that probably occurred during warmer intervening periods did not completely destroy all the pre-existing palsas.…”
Section: Regional Settingmentioning
confidence: 94%
“…Lithalsas can be encountered in discontinuous permafrost regions (Zoltai and Tarnocai, 1975;Washburn, 1983;Zuidhoff, 2002). A large concentration of such landforms exists along the eastern coast of Hudson Bay, where these features have developed during the Late Holocene period in emerged post-glacial marine silts (Dionne, 1978;Seguin and Allard, 1984;Allard et al, 1987a;Allard and Rousseau, 1999;Payette et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Permafrost inception started in the mid-to late Holocene, culminating during the Little Ice Age. Palsas and lithalsas, formed by ground ice aggradation and related surface heaving, are widespread in the region and typical of the discontinuous permafrost landforms in subarctic Québec (Allard and Seguin 1987). Recent increases in air/ground temperatures and snow cover along the eastern shore of Hudson Bay have contributed to widespread reduction of permafrost extent, resulting in increasing surface areas occupied by subarctic thermokarst ponds (Payette et al 2004;Vallée and Payette 2007;Jolivel and Allard 2013).…”
Section: Key Paleolimnological Findings From Thermokarst Lake Archivesmentioning
confidence: 99%